Pengaruh Musik Mozart terhadap Memori pada Pelajaran Menghafal di SMP Ta’miriyah Surabaya - Suhadianto, Suhadianto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
The purpose of this study was to prove whether there is influence of Mozart's music on memory usage on memorizing lessons in Ta'miriyah Junior High School Surabaya. This type of research is True Experimental Design with The Posttest-Only Groups Equivalent Design. Subjects were students of class VII Ta'miriyah Surabaya, N = 40 with the distribution of 20 subjects as the control group and 20 subjects as an experimental group were randomly selected from 183 students using computer technique selection. The data collection conducted research using the technique recall, by asking research subjects to memorize verses in the Al-Buruuj has been learned during the study. Statistical analysis was performed using parametric statistical t-test student. Statistical analysis showed the value t = 3,402 p = 0.003 (p <0:01). This shows a significant difference of the number of verses in the Al-Buruuj that can be memorized by the experimental group and the control group. Thus the research hypothesis which says there is influence of Mozart's music to memory in memorizing lessons in Ta'miriyah Junior High School Surabaya accepted.Keywords : Memory, Mozart Music